On conformal transformation of $Ξ$-curvature - Narges Panahi; Bahman Rezaei; Akbar Tayebi (AUT Journal of Mathematics and Computing)
In this paper, we study the conformal transformation of recent defined non-Riemannian curvature in Finsler Geometry, namely $Ξ$-curvature. Indeed, we obtain the necessary and sufficient condition under which the conformal transformation preserves the $Ξ$-curvature.